First high–resolution analysis of the 2ν1(A1) and ν1+ν3(F2) interacting states of 72GeH4 and 73GeH4. (October 2019) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Raspopova, N.I.; Koshelev, M.A.; Velmuzhova, I.A.; Sennikov, P.G.; Bulanov, A.D.; Kuznetsov, A.V.; Leroy, C.
Highlights: The 2 v 1 / v 1 + v 3 interacting states of GeH4. Resonance interactions in spherical top molecules. Determination of spectroscopic parameters. Abstract: The spectra of germane 72 GeH4 and 73 GeH4 enriched up to 99.9 % were recorded with high resolution (0.003 cm − 1 ) at different pressures with the Bruker IFS 125HR Fourier transform spectrometer (Nizhny Novgorod, Russia). The region of 4020–4260 cm − 1, where the 2 ν 1 ( A 1 ) and ν 1 + ν 3 ( F 2 ) bands are located, was theoretically analyzed. The 2025 and 1774 transitions with J max = 21 were assigned to these bands of the 72 GeH4 and 73 GeH4 species. Rotational, centrifugal distortion, tetrahedral splitting, and interaction parameters of the (2000, A 1 ) and (1010, F 2 ) vibrational states were determined from the fit of experimental line positions of both isotopologues. The obtained sets of 13/13 fitted parameters reproduce the initial 2025/1774 experimental line positions with a d rms = 2.9 × 10 − 4 cm − 1 and d rms = 2.7 × 10 − 4 cm − 1 (for 72 GeH4 and 73 GeH4, respectively).